Myoepithelioma of the Palate: A Case Report - Morikawa, Tetsuro; Paudel, Durga; Onishi, Aya; Hiraki, Daichi; Adhikari, Bhoj Raj; Neopane, Puja; Harada, Fumiya; Utsunomiya, Masafumi; Yoshida, Koki; Sato, Jun; Nishimura, Michiko; Abiko, Yoshihiro (UI Scholars Hub, 2017)
Myoepithelioma, a benign tumor, occurs with a frequency of 1.5% among all salivary gland tumors, and it most commonly affects the parotid gland. Nearly the entire epithelium is composed of neoplastic myoepithelial cells exhibiting spindle, plasmacytic, epithelial-like, and clear cells. Case Report: A 52-year-old woman with myoepithelioma of the palate. The patient was referred to our hospital with a chief complaint of swelling on the right side of the palate. Following clinical and intraoral examinations, the tumor was removed under general anesthesia. Viewed microscopically, the tumor was seen to be surrounded by a fibrous membrane, primarily composed of a solid growth of neoplastic myoepithelial cells, virtually surrounding a hyaline-like eosinophilic substance. Immunohistochemical examination revealed strongly-positive reactions by the tumor cells for wide-spectrum cytokeratin (CK wide), vimentin, and S-100 proteins. CK 7, smooth muscle actin (SMA), p63, and glial fibrillary acidic protein (GFAP) gave weakly-positive reactions. Conclusion: Based on the findings, a pathological diagnosis of myoepithelioma was reached.